Microsoft office excel 2007 inside out - Dodge, Mark (Microsoft Press, 2007)
Learn everything you need to know for working with Microsoft Office Excel 2007--from the inside out! This book packs hundreds of time-saving solutions, troubleshooting tips, and workarounds for using Office Excel 2007--all in concise, fast-answer format. Whether you are upgrading from Office 97 or Office 2003, you'll be able to dig in to the work-ready resources that help you take your Office Excel 2007 experience to the next level. This information-packed complete reference shows you how to get the most out of Office Excel 2007. You will learn how to navigate the product's new features and capabilities, including the new formatting and editing advances such as Live Preview. You'll explore new graphics capabilities, master the charting interface, and learn how to create dynamic lists with PivotTable® reports. You'll even learn how to automate Office Excel with macros, custom functions, and more. Plus, you'll get tools, eBooks, and more on the companion CD. With INSIDE OUT, you get all muscle and no fluff!